Oxidative Stress in Retinal Degeneration Promoted by Constant LED Light - Benedetto, Maria M.; Contin, Maria A. (Frontiers in Cellular Neuroscience, 2019)
Light pollution due to environmental artificial light, may accelerates degenerative diseases or induce retinal degeneration and circadian asynchrony. The excess of light exposure is a rapidly growing problem in the actual societies, so studies on the consequences of long-term exposure to low levels of light are needed to determine the effects on vision. A better understanding of the molecular mechanisms of light damage may provide valuable insights into the progression of clinical disorders related to phototransduction defects caused by light pollution. Several animal models have been used to study retinal degeneration by light, however, some important aspects remain to be established. Previously, we demonstrate that cool white treatment of 200 lux LED produces retinal remodeling with rods and cones cell death and significant changes in opsin expression in the inner nuclear layer and ganglion cell layer. Therefore, to further development describing the molecular pathways of retinal degeneration, here, we have examined the oxidative stress and changes in the fatty acid composition in rat retinas exposed to constant light. We demonstrated the existence of oxidative reactions after five days in outer nuclear layer, corresponding to classical photoreceptors; catalase enzyme activity did not show significant differences in all times studied and the fatty acid study showed that docosahexaenoic acid decreased after four days. Remarkably, the docosahexaenoic acid diminution showed a correlation with the rise in stearic acid indicating a possible association between them. We assumed that the reduction in docosahexaenoic acid may be affected by the oxidative stress in photoreceptors outer segment which in turn affects the stearic acid composition with consequences in the membrane properties. All these miss-regulation affects the photoreceptor survival through unknown mechanisms involved. We consider that oxidative stress is one of the many pathways involved in retinal degeneration induced by light.